Brain Death: A Conclusion in Search of a Justification - Shewmon, D. Alan (The Hastings Center report, 2018)
At its inception, “brain death” was proposed not as a coherent concept but as a useful one. The 1968 Ad Hoc Committee of the Harvard Medical School to Examine the Definition of Brain Death gave no reason that “irreversible coma” should be death itself, but simply asserted that the time had come for it to be declared so. Subsequent writings by chairman Henry Beecher made clear that, to him at least, death was essentially a social construct, and society could define it however it pleased. The first widely endorsed attempt at a philosophical justification appeared thirteen years later, with a report from the President's Commission for the Study of Ethical Problems in Medicine and Biomedical and Behavioral Research and a seminal paper by James Bernat, Charles Culver, and Bernard Gert, which introduced the insightful tripartite scheme of concept, criterion, and tests for death. Their paper proposed that the correct concept of death is the “permanent cessation of functioning of the organism as a whole,” which tenuously remains the mainstream concept to this day. In this essay, I focus on this mainstream concept, arguing that equating brain death with death involves several levels of incoherence: between concept and criterion, between criterion and tests, between tests and concept, and between all of these and actual brain death praxis.